Studies on carbonate ion transport through supported liquid membrane using primene JMT and tributyl phosphate - Gaikwad, Abaji G. (Separation Science and Technology, 2009)
A supported liquid membrane system consisting of source, receiving and membrane phases, in which mixed extractants were used in the membrane phase, was explored for the carbonate ion transport from source to receiving through membrane phase. Primary amine Primene JMT and TBP were used as extractants (carriers) in liquid membrane phase. Different experimental variables such as concentration of carbonate ion, carriers, alkali and hydrogen peroxide, stirring speed, etc have been investigated. Primary amine Primene JMT and TBP mixed carriers show the synergistic effect for the transport of carbonate ions through supported liquid membrane system. The stability of the supported liquid membrane system has been explored for 50 h. The pre-concentration of carbonate ions from dilute solutions were also demonstrated. The effect of different alkalis on the permeability coefficient of transport of carbonate ions through supported liquid membrane system has been investigated. The primary amine in combination with TBP shows more effective for the transport of carbonate ions through supported liquid membrane system in comparison with that of secondary and tertiary amines.
Keywords: carbonate ion; primary amine primene JMT; supported liquid membrane; synergistic effect; tributyl phosphate (TBP)